Analysis and design of a tilted rotor hexacopter for fault tolerance - Giribet, Juan Ignacio (2016)
A proof is presented of how a hexagon-shaped hexacopter can be designed to keep the ability to reject disturbance torques in all directions while counteracting the effect of a failure in any of its motors. The method proposed is simpler than previous solutions, because it does not require change of the motor rotation direction or in-flight mechanical reconfiguration of the vehicle. It consists of tilting the rotor a small fixed angle with respect to the vertical axis. Design guidelines are presented to calculate the tilt angle to achieve fault-tolerant attitude control without losing significant vertical thrust. It is also formally proved that the minimum number of unidirectional rotating motors needed to have fault tolerance is 6 and that this can be achieved by tilting their rotors. This proof is essentially a control allocation analysis that recovers in a simple way a result already known: the standard configuration (without tilting the motors) is not fault tolerant. A simulation example illustrates the theory.